Tinjauan Ilmu Falak Dan Fiqh Hisab Rukyah Terhadap Koreksian Daerah Jadwal Salat - jayusman jayusman (University of Muhammadiyah Sumatera Utara, 2021)
There was a list of regional corrections in the prayer schedule. Falak experts differ in the use of the corrected conversion prayer schedule for this area. The focuses of this paper were: How is the basis for calculating regional corrections? And How is the review of Falak experts and fiqh Hisab Rukyah using the conversion prayer schedule from district corrections? Conclusion: The basis for calculating regional corrections in the prayer schedule was related to the difference in the longitude of the place. A difference of 1 longitude was equivalent to 4 minutes. Regional corrections presented were the result of rounding. There were district corrections where the difference was a little. There were correction data for areas that differ significantly. Regional corrections were only limited to cities or areas adjacent to that city. Its use was not as an initial guideline for prayer times in far distant places.